Studi Komparasi Teori Pembelajaran ‘Athiyah Al-Abrasyi dan Pendidikan Karakter Serta Relevansinya dengan Pendidikan Islam - Bagas Ilham Yudhiyantoro (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2022)
AbstractLearning is basically a process, an organizing process, the process of regulating the environment around the student's environment, so that it can encourage and motivate students so that there is a willingness to carry out the learning process. Learning can also be said as a step in providing assistance or guidance to students in the learning process. To form intelligent people, schools not only develop mastery in the academic field, but also in accordance with national education goals. The use of media by children in the educational process must also be supervised by parents and educators, if the child is not supervised by parents or educators, the child will lose control over himself, including the child's religious character. Character education has experienced a decline in the quality of society, many incidents have happened to school children such as pornography, violence, brawls and others. To prevent this, character education must be implemented and implemented in formal education at all levels of education in Indonesia. The purpose of this study was to compare the learning theory of 'Athiyah Al-Abrasyi and Character Education and its relevance to Islamic education. This study uses library research methods (library research). Sources of data come from books and related journals. The results of this study state that the learning concept offered by 'Athiyah Al-Abrasyi is more directed to moral education based on spiritual/religious values, the learning theory of 'Athiyah Al-Abrasyi has shortcomings which are considered as problems in learning. education World. while the lack of character education theory is the absence of a special curriculum in the implementation of character education and the relevance of Islamic education to the learning theory of 'Athiyah Al-Abrasyi and character education is found in the learning method.Keywords: Learning, 'Athiyah Al-Abrasyi, Character Education, Islamic Education